2021
DOI: 10.4081/monaldi.2021.1636
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis at the Pulmonary Medicine Department of a tertiary care hospital in Mumbai. Our experience and The New Modified Criteria Clinical Radiological Physiological (TNMC CRP) score for sarcoidosis: A novel proposition to assess the functional status

Abstract: Sarcoidosis is a multisystemic granulomatous disease most commonly involving the pulmonary system and having a myriad of manifestations. However literature is scanty pertaining to the profile and scoring system in sarcoidosis. This study was undertaken to understand the profile of sarcoidosis and an endeavor to assess the functional status with a simplified scoring system. This was an observational study undertaken in the department of Pulmonary Medicine at a tertiary care. The profile of these patients was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…In this study x ray of sarcoidosis shows bilateral hilar lymphadenopathy (100%) which is similar to that of the study of Ketaki Utpat, Chinnu Sasikumar, Unnati Desai, et al in which 95% of cases shows bilateral hilar lymphadenopathy [22].…”
Section: Discussionsupporting
confidence: 90%
“…In this study x ray of sarcoidosis shows bilateral hilar lymphadenopathy (100%) which is similar to that of the study of Ketaki Utpat, Chinnu Sasikumar, Unnati Desai, et al in which 95% of cases shows bilateral hilar lymphadenopathy [22].…”
Section: Discussionsupporting
confidence: 90%
“…Three studies were removed for duplicated data used in another study ( 13 , 20 , 21 ). Finally, the analysis included 25 studies ( 7 , 11 , 12 , 22 43 ). The studies were conducted in the United States ( n = 10), Europe ( n = 9), and Asia ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies ( 11 , 22 24 , 30 36 , 38 , 40 , 42 ) reported the prevalence of SAPH by TTE. Among them, one study targeted a population with advanced sarcoidosis, among which the prevalence of SAPH by TTE was 29.7% ( 11 ).…”
Section: Resultsmentioning
confidence: 99%